Influence of temperature on an Anammox sequencing batch reactor (SBR) system under lower nitrogen load. (December 2018) - Li, Quan; Wang, Shaopo; Zhang, Pengda; Yu, Jingjie; Qiu, Chunsheng; Zheng, Jianfeng
Graphical abstract: Highlights: Anammox bacterial was enriched in SBR system under lower nitrogen load. 15–26 °C constitutes breaking point for nitrogen removal in the Anammox SBR. Temperature variation can affect Anammox bacteria community structure. Ca. Kuenenia is more adaptive to varied temperature than Ca. Brocadia . Abstract: The nitrogen removal performance and microbial communities of an Anammox sequencing batch reactor (SBR) was studied under varied temperatures with a lower nitrogen loading rate (NLR) about 0.28 kgN/m 3 /d. Results showed that the temperature could influence the nitrogen removal performance and the community structure in the Anammox SBR system. Under lower temperatures, both the nitrogen removal efficiencies and Anammox activity were in lower levels. When temperature was raised again, the Anammox activity recovered accordingly. When the temperature dropped from 33 ± 1 °C to15 °C, the dominant Anammox bacteria shifted from Ca. Brocadia to Ca. Kuenenia in the sludge. When the temperature returned over, the abundance of Ca. Brocadia recovered, while the Ca. Kuenenia was still the dominant Anammox bacteria. This indicated that Ca. Kuenenia is more adaptable to low temperature environment than Ca. Brocadia under low NLR with temperature variation.